Running Dry : Essays on Energy, Water, and Environmental Crisis - Jones, Toby Craig, 1972- (Pinpoints (Series), 2015)
The world's water is under siege. A combination of corporate greed, the elite pursuit of political power, and our unrelenting reliance on carbon-based energy is accelerating a broad range of environmental and political crises. Potentially catastrophic climate change, driven primarily by the consumption of oil and gas, threatens the environment in a variety of ways, including producing unprecedented patterns of heavy weather and superstorms in some places and droughts in others. Alongside intensifying environmental dangers posed by our reliance on carbon energy, the conditions of modern life, from happiness to the possibility of democratic politics, are also being undermined. In Running Dry, historian Toby Craig Jones explores how modern society's unquenchable thirst for carbon-based energy is endangering the environment broadly, as well as the historical roots of this threat. This accessible book examines the history of the "energy-water nexus," the ways in which oil and gas extraction poison and dry up water resources, the role of corporate "science" in deflecting attention away from the emerging crises, and the ways in which the rush to capture more energy is also challenging America's democratic order.